Can we say no? : the challenge of rationing health care - Aaron, Henry J. (Brookings Institution Press, 2005)
"Examines the use of rationing as a means to curb health care spending, using the experience of Great Britain to highlight the promises and pitfalls of this approach"--Provided by publisher